Bone marrow lesion and medial meniscus extrusion width changes following arthroscopic partial meniscectomy for medial meniscal flap tears - Hitoshi Sekiya; Kenzo Takatoku; Hitoshi Okami; Yuji Kanaya; Kenta Yanagisawa (Journal of Orthopaedic Surgery and Research, 2025)
Abstract Background The current literature evaluating meniscectomy outcomes often mixes various tear patterns, failing to elucidate the impact of specific tear types on procedure results. Flap tears, which are prone to causing mechanical symptoms, require targeted research. This study aims to examine Lysholm scores following a meniscectomy for medial meniscus flap tears, to determine if extensive resections lead to poorer one-year outcomes, and to assess their impact on postoperative bone marrow lesion (BML) risk and medial meniscus extrusion (MME) width. Methods Patients undergoing arthroscopic meniscectomy for medial meniscal flap tears were classified into three groups: minimum resection, single leaf resection, and subtotal resection. Lysholm scores and medial joint space (MJS) width on Rosenberg view radiographs were measured preoperatively and one year postoperatively. BMLs and MMEs were assessed via MRI preoperatively and at 1, 3, 6, and 12 months postoperatively. Results Fifty patients (mean age 60 ± 13 years) underwent meniscectomy: minimum resection in 21 (42%), single leaf in 23 (46%), and subtotal in 6 (12%). The Lysholm scores improved significantly, from 65.5 ± 17.6 to 93.4 ± 16.5 (n = 50) at 12 months in patients overall (p < 0.001), while MJS width decreased from 3.9 ± 0.7 mm to 3.5 ± 0.8 mm (p < 0.001). There were no significant differences in Lysholm scores or MJS widths among the three resection patterns. The occurrence rate of BMLs in the medial femoral condyle and tibial plateau increased post-surgery, peaking at 1 month, but then improved to near-baseline by 12 months. The occurrence rate of BMLs was higher in the single leaf and subtotal meniscectomy groups post-surgery, but declined across all groups by 12 months. Among the three groups with different resection patterns, MME width at 12 months was 2.7 ± 1.8 mm in the subtotal resection group, which was significantly larger than in the other groups. Conclusions Arthroscopic partial meniscectomy for flap tears yielded favorable 12-month outcomes. Larger resections were associated with greater BML incidence and greater MME width.